Determinants of exchange rate fluctuation in Malaysia / Syed Mohamad Akif Syed Sheikh - Syed Sheikh, Syed Mohamad Akif (Faculty of Business and Management, 2018)
This paper aims to investigate the fluctuation of the exchange rate in Malaysia. The study will focus on the exchange rate of Malaysian Ringgit (MYR) against US dollar (USD) since Malaysia as one of the strongest currency in Asia and US dollar is the global currency accepted for the most international transaction. The exchange rate variables included in this studies are the inflation rate, money supply, and interest rate. The purpose of the studies is to find the relationship between dependent variable and independent variable, whether they have any correlation between each other or not. The studies used quantitative secondary data which is time series data and multiple regression models as the technique to look at the fluctuation of Malaysian Ringgit. There will be 82 observation over the period of 1997 QI until 2017 Q2 that derived from Thomson Reuters Datastream. The expected finding showed interest rate, money supply, and inflation rate have a significant influence on the movement of the exchange rate. This showed that macroeconomics variable is very important to indicate the value of a currency. Therefore, policymakers should be aware of controlling mechanics that affecting the exchange rate, so that the movement of any determinants will not run adverse to the market mechanism